What are the main drivers behind Ethiopian farmers soil and water conservation practices - Dufourny N. (2012)
The present report describes the internship done at the ILRI Research Center of Addis Ababa (Ethiopia) from May 2011 to August 2011. This internship was required for the fulfillment of a Masters degree in Economics at the Universit Catholique de Louvain (Belgium). This report is structured in three sections, a description of the host organization along with the internship topics and objectives and the methods solicited. The analysis related to the economical question about the drivers of soil and water conservations adoption and a personal evaluation of the experience are then presented. The internship project was formally reviewed and redesigned based on work embodied in the Nile Basin Development Challenge (NBCD).